REFLECTIONS OF GUNUNGPATI SOCIETY’S LEXICON ON THE FOLKLORE OF GOA KREO IN SEMARANG CITY AS PETILASAN SUNAN KALIJAGA (ETNOLINGUISTIC STUDIES) - Sifa Destry Fauzia; Wakit Abdullah Rais; Dwi Purnanto (English Language and Literature International Conference (ELLiC) Proceedings, 2021)
This research is based on improving the oral culture (folklore) and native language which is an intellectual wealth of a nation. Folklore is an oral culture that is passed down through generation to generation in its submission and defense. Whereas in the modern generation that desperately needs more attention to keep preserving it. This research aims to find out the reflections of Gunungpati society's lexicon on the folklore of Goa Kreo as a petilasan of Sunan Kalijaga in Semarang City. Folklore of Goa Kreo as  petilasan of Sunan Kalijaga became the beginning of  Sesaji Rewanda tradition in Gunungpati Semarang. The research method used is qualitative descriptive.  The data collection in this research uses participation observation techniques, in-depth interviews, library studies and documents. The data that has been obtained is analyzed with an ethnolinguistic approach, then the data analysis technique is done by ethnographic analysis methods covering domains, taxonomy, and components. The results of analysis this research data are the forms of lexicon of Gunungpati society on the Goa Kreo’s folklore in the form of lingual units including of monomorphists, polymorphists, phrases and clauses. The folklore lexicons of Goa Kreo in Javanese have cultural, lexical and contextual meanings that reflecting the local wisdom of Gunungpati society.